2019
DOI: 10.2478/pomr-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thermo-chemical Technologies for Conversion of Associated Gas in Diesel-Gas Turbine Installations for Oil and Gas Floating Units

Abstract: The paper considers the issue of thermo-chemical recovery of engine’s waste heat and its further use for steam conversion of the associated gas for oil and gas floating units. The characteristics of the associated gas are presented, and problems of its application in dual-fuel medium-speed internal combustion engines are discussed. Various variants of combined diesel-gas turbine power plant with thermo-chemical heat recovery are analyzed. The heat of the gas turbine engine exhaust gas is utilized in a thermo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Investigations carried out earlier by the current authors have made it possible to identify the main parameters that influence the process of associated gas conversion [26]. It was found that an increase in the process pressure leads to an increase in the temperature, which is necessary for effective conversion.…”
Section: Characteristics Of the Processes In A Gas Turbine Combustor mentioning
confidence: 90%
See 1 more Smart Citation
“…Investigations carried out earlier by the current authors have made it possible to identify the main parameters that influence the process of associated gas conversion [26]. It was found that an increase in the process pressure leads to an increase in the temperature, which is necessary for effective conversion.…”
Section: Characteristics Of the Processes In A Gas Turbine Combustor mentioning
confidence: 90%
“…Associated gas was adopted as the initial fuel, with the following composition (vol. ): methane (CH 4 ) 62.8-73.7%; ethane (C 3 H 8 ) 6.7-17.7%; propane (C 2 H 6 ) 6.1-9.0%; butane (C 4 H 10 ) 2.4-5.0%; pentane and heavier (C5+) 1.0-3.7%; carbon dioxide (CO 2 ) 0.6-9.2%; nitrogen (N 2 ) 0.0-4.4%; hydrogen sulfide (H 2 S) 0.0-2.8 [26,28]. Since the gas temperature behind the steam generator was above the dew point temperature, the maximum allowable steam/gas mass ratio was 6-7, depending on the composition of the associated gas.…”
Section: Characteristics Of the Processes In A Gas Turbine Combustor mentioning
confidence: 99%
“…Two 250 kW high-temperature SOFC systems working with methanol were integrated within the ship supplying electrical energy. Cherednichenko and Serbin (2018) and Cherednichenko et al (2019) analysed the capabilities of thermo-chemical technologies for the conversion of different hydrocarbons on ships. As reported by Sun et al (2010), the SOFC-GT system for the Large Medium Speed Roll-on/Rolloff sealift ship has significant potential in reducing nitrogen oxides emission and fuel consumption.…”
Section: Intoductionmentioning
confidence: 99%
“…The applicability of thermo-chemical technologies for converging of associated gas in diesel-gas turbine installations for oil and gas floating units was considered in [8]. To describe the processes in the combustion chamber of a gas turbine engine working on synthesis gas, a mathematical model with detailed 35-reaction chemical mechanism was used.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…To describe the processes in the combustion chamber of a gas turbine engine working on synthesis gas, a mathematical model with detailed 35-reaction chemical mechanism was used. The disadvantage of the proposed in [8] calculation model is the impossibility of predicting the higher hydrocarbons burning-out, which play a significant role in the associated gas oxidation process.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%